Geographical information systems theory, applications and management : 4th international conference, GISTAM 2018, Funchal, Madeira, Portugal, March 17-19, 2018 : revised selected papers /: 4th international conference, GISTAM 2018, Funchal, Madeira, Portugal, March 17-19, 2018 : revised selected papers. ([2019]) - Unknown
No abstract available